Does facial appearance of dentofacial deformity influence the need for orthognathic surgery: The Malaysian perception - Abdul Halim Chong, Fatin Halini; Md Salleh, Siti Nuriyah; Abu Bakar, Noraini; Ismail, Izzati Nabilah Binti (World Scientific, 2019)
Aim: This study evaluates the perception towards facial appearance in dentofacial deformity and the need for orthognathic surgery among public with and without dental backgrounds. Materials and methods: A hundred participants were recruited to participate in the questionnaire. The questionnaire consists of 12 facial photographs of cases with dentofacial deformity or malocclusion in varying severity. The perception of facial appearance (FAS), treatment need score (TNS) and knowledge regarding dentofacial deformity were used for evaluation. Results: There were significant differences between dental and non-dental when assessing their knowledge in all the questionnaire items (p<0.05). When FAS and TNS were assessed between dental and non-dental, there were no significant differences in the mean of FAS and TNS in all the presented cases (normal, borderline, severe). Pearson correlation between perceived FAS and TNS showed statistically negative correlation for severe and normal cases, whereby a decrease in FAS for severe cases showed an increase in the TNS, and an increase in FAS for normal cases showed a decrease in TNS.